2009
DOI: 10.21236/ada498162
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Scalability: Designing Interfaces and Algorithms for Soldier-Robotic Swarm Interaction

Abstract: Vehicle Technology Directorate, ARLApproved for public release; distribution unlimited. ii REPORT DOCUMENTATION PAGE Form Approved OMB No. 0704-0188Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection information. Send comments regarding this burden estimate or any other aspect of this collection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…As with Haas et al [3], we found that temporal binding time for touch-first commands was significantly shorter than for speech-first commands, no matter what the level of workload. However, temporal binding time for speech-first commands was perceived to be two times greater than touch-first commands in the presence of the secondary task, while this difference was less in conditions with no workload.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…As with Haas et al [3], we found that temporal binding time for touch-first commands was significantly shorter than for speech-first commands, no matter what the level of workload. However, temporal binding time for speech-first commands was perceived to be two times greater than touch-first commands in the presence of the secondary task, while this difference was less in conditions with no workload.…”
Section: Discussionsupporting
confidence: 88%
“…Other researchers [2] found that multimodal controls for dynamic maps allows users to choose which input modality they want to use, in which order, when inputting information. Haas, Fields, Stachowiak, Hill and Pillalamarri [3] explored the use of multimodal touch and speech controls in a dynamic map display to allow U. S. Army Soldiers to maintain supervisory control of a simulated robotic swarm (a large number of small, relatively simple robots capable of autonomous travel and operation) to provide sentry protection to a simulated convoy of four vehicles. These researchers found that multimodal speech and touch control allowed efficient Soldier supervisory control of a dynamic map display showing swarm and convoy spatial information.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides displays, multimodal feedback to the operator has also been investigated [98]. Here, the authors used a potential field approach for controlling the swarm for a convoy protection scenario and designed an interface that provides feedback regarding the swarm speed, strength, capability, and dispersion.…”
Section: Swarm State Estimation and Visualizationmentioning
confidence: 99%
“…For example, a study on soldier-robotic swarm interactions suggested that use of multimodal (visual, auditory and tactile) display techniques influences the effectiveness and efficiency of supervisors. 33 The level of autonomy available in the robotic system can affect supervisor workload as well. 2,34 Automation is often employed to address the problem of high workload.…”
Section: The Effects Of High Workloadmentioning
confidence: 99%